Crawler Crane Failure Cause Analysis Using Fishbone Diagram, Pareto Principle, and Failure Mode Effect Analysis: A Comprehensive Approach to Minimize Downtime and Improve Operational Reliability - Faisal, Rahman; Firda, Herlina; Yassyir, Maulana; Ice, Trianiza; Saifullah, Arief (INTI International University, 2025)
Crawler cranes are critical heavy equipment in the construction industry, but they often experience failures that cause downtime and increased costs. This article comprehensively analyses crawler crane failures using three main methods: Fishbone Diagram, Pareto Principle, and Failure Mode and Effect Analysis (FMEA). Failure data for the past two years (January 2022 – September 2024) is analyzed to identify root causes and determine repair priorities. A Fishbone Diagram is used to identify the main causes of failure, which are grouped into four categories: Mechanical, Electrical, Environmental, and Human Error. From this analysis, it is found that mechanical failure is the most dominant cause. This analysis found that mechanical failure is the most dominant cause, mechanical failures account for most failures (60%), followed by electrical failures (33%), with failures in the gearbox and engine overheating being the most significant causes. Furthermore, FMEA evaluates potential failure modes, determines their impacts, and sets mitigation priorities based on the Risk Priority Number (RPN). The results of this study provide a strategic approach to minimize downtime by focusing maintenance efforts on the root causes of failure. This article also offers a new contribution by combining three comprehensive analysis methods not systematically applied to crawler crane maintenance. This research is expected to help improve operational reliability and reduce repair costs in the construction industry.